2023
DOI: 10.1371/journal.pone.0285805
|View full text |Cite
|
Sign up to set email alerts
|

Trends of infant vaccination timeliness and completion in selected urban slum communities in Ibadan, Southwestern Nigeria: A four-year review

Abstract: Background Suboptimal infant vaccination is common in Nigeria and multiple interventions have been deployed to address the situation. Child health indicators are reported to be worse in urban slums compared with other urban areas, but urban data are usually not disaggregated to show these disparities. Examining the timeliness and completion of infant vaccination in urban slums is important to determine the effectiveness of existing interventions in improving infant vaccination among this vulnerable population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Presently, over 2.3 million doses of the vaccine, after proven efficacy and safety have been administered in three African countries [ 5 , 6 ]. A comprehensive study on the pooled coverage of full immunization among children in some parts of Nigeria showed that only 0.6% infants had a complete and timely vaccination [ 11 ]. Recent evidence had suggested that vaccine “hesitancy”—a delay in the willingness to accept or refuse vaccine despite its availability, contributed to the low acceptance of the vaccine among Nigerian children [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, over 2.3 million doses of the vaccine, after proven efficacy and safety have been administered in three African countries [ 5 , 6 ]. A comprehensive study on the pooled coverage of full immunization among children in some parts of Nigeria showed that only 0.6% infants had a complete and timely vaccination [ 11 ]. Recent evidence had suggested that vaccine “hesitancy”—a delay in the willingness to accept or refuse vaccine despite its availability, contributed to the low acceptance of the vaccine among Nigerian children [ 12 ].…”
Section: Introductionmentioning
confidence: 99%